Clinical profile and radiological pattern in follow-up study of patients treated for moderate-to-severe COVID-19 pneumonia - Vijayakumar; Apoorva Ravi; V Pranavi (Wolters Kluwer Medknow Publications, 2023)
The COVID-19 pandemic is the modern-day apocalypse that the world has experienced, with a death toll of 60.1 lakh by 2022. Although many patients recovered from the disease, a major part of the population has been crippled with the sequelae that occurred with the infection. One such complication is the development of pulmonary fibrosis, especially among those who recovered from moderate-to-severe COVID-19 infection that has been reported in several studies. Albeit adequate and early usage of antivirals, antibiotics, and steroids, and the development of lung fibrosis was inevitable in certain patients. Here, we report four cases, who recovered from COVID-19 infection but developed pulmonary fibrosis along the course of illness. They were followed for 6 months, along with treatment with antifibrotics, and were assessed for improvement, both clinically and radiologically. While three among the four patients showed resolution in their follow-up CT scans, one patient's fibrosis worsened with progression to interstitial lung disease.